In hypertensive individuals, sleep time and sleep efficiency did not affect the number of angina episodes: a cross-sectional study - Ahmad H. Alghadir; Masood Khan; Mohammed Mansour Alshehri; Abdulfattah S. Alqahtani; Mishal Aldaihan (Scientific Reports, 2022)
Abstract Previous studies have reported adverse effects of short and long sleep duration on cardiovascular health. However, how sleep time and sleep efficiency affect angina have not been studied in hypertensive individuals. This study aimed to assess the relationship of sleep with angina. Using a cross-sectional design, data from 1563 hypertensive individuals were collected from the parent Sleep Heart Health Study (SHHS). Age, alcohol use, average diastolic blood pressure (ADBP), average systolic blood pressure (ASBP), cigarette use, sleep time, sleep efficiency, percent time in stage N3 of sleep, and body mass index (BMI) were used as covariates. Multiple linear regression, the Chi-Square test, and Pearson’s correlation coefficient were used for data analysis. Unadjusted sleep efficiency, sleep time, ADBP, and age were significant (p < 0.05) predictors of the number of angina episodes (Anginan). When the covariates were adjusted, only ADBP and ASBP were significant (p < 0.05) predictors of Anginan. Sleep efficiency, BMI, ADBP, sleep time, and age had a significant (p < 0.05) correlation with Anginan. In hypertensive individuals, sleep time and sleep efficiency did not affect Anginan when adjusted for covariates. ADBP and ASBP were found to be significant predictors of Anginan when the covariates were adjusted.